Task-dependent neural correlates of the processing of verbal threat-related stimuli in social phobia - Schmidt, Stephanie; Mohr, Alexander; Miltner, Wolfgang H. R.; Straube, Thomas (Biological Psychology, 2010)
The neural basis of abnormal processing of phobia-related linguistic cues in individuals suffering from social phobia is unknown, particularly in respect to different task conditions. Using event-related functional magnetic resonance imaging, this study investigated brain activation to phobia-related and phobia-unrelated words in 19 socially phobic patients and 18 healthy control subjects (HC) while subjects had to attend either to social meaning or to grammatical category of words (direct or indirect task). During the indirect task, patients, compared to HC, showed an increased activation of the amygdala and orbitofrontal cortex (OFC) in response to phobia-related vs. phobia-unrelated words. Activation of the insula was positively correlated with patients' symptom severity during the direct task. The results suggest a specific role of the amygdala and OFC during the processing of verbal phobia-relevant distracting information. In contrast, insula activation seems to be more important for direct processing of disorder-related words, especially in more severe cases of social phobia. © 2010 Elsevier B.V.
Created from Fastlane, Scopus look-up
Keywords: Amygdala; Attention; FMRI; Insula; Social phobia; Words